Fasilitasi HITARO (Hidup Tanpa Rokok) di MTS Al-Ittihad Kecamatan Sawangan Kota Depok - Sayyed Muhammad Al Fajr; Nur Rizky Ramadhani; Ade Ashar Rahayu; Al Farel Dimas Wibisono; Sausan Salsabillah; Siti Damayanti; Sukmawati Boru Saragih (Sagamedia Indo Press, 2023)
Introduction: Cigarettes are processed tobacco products that are packaged, and produced from the Nicotiana Tabacum, Nicotiana Rustica and other species or their synthetics containing nicotine and tar with or without additives. together is the bad behavior of smoking. Objectives: This activity aims to facilitate public health regarding the dangers of smoking in MTS Al-Ittihad, Sawangan District, Depok City. Method: This public health facilitation activity was carried out on August 10, 2022. The target of this activity was MTs Al-Ittihad students. The method used in this community service activity is to carry out socialization in the form of material presentation and group discussions. Result: The results of the study as many as 31 students of MTS Al-Ittihad, the level of student knowledge about the dangers of smoking was known to be 9 students with a percentage of 29% less aware of the dangers of smoking and 22 students with a percentage of 71% knowing the dangers of smoking. Conclusion: Based on the results of the activities above, it can be concluded that there are differences in students' knowledge before and after the implementation of socialization about the dangers of smoking. there was an increase in knowledge and understanding of the dangers of smoking for students at MTS Al-Ittihad after this community service was held.